Rapid Social Registry Assessment : Malawi's Unified Beneficiary Registry - Lindert, Kathy (World Bank, Washington, DC, 2018)
This paper reports on a rapid assessment of Malawi’s integrated social registry, known as the Unified Beneficiary Registry (UBR). The timing of the assessment was ripe given the upcoming round of continued expansion of the UBR and a planned shift in registration targets (from 50 percent to 100 percent of households). As such, the objectives of this assessment are to: (a) review the UBR experience to date; (b) identify strengths and areas for improvement; (c) provide short-term recommendations to support the upcoming expansion, including implementation adaptations that would be needed to accommodate the revised registration targets; and (d) support the longer-term strengthening of the UBR. While primary audience for this paper includes the core stakeholders in Malawi, the report is also of potential interest to other countries interested in developing social registries and/or carrying out social registry assessments.